2016
DOI: 10.4068/cmj.2016.52.2.91
|View full text |Cite
|
Sign up to set email alerts
|

Vilazodone for the Treatment of Depression: An Update

Abstract: Vilazodone is a novel antidepressant having a selective serotonin (5-HT) reuptake inhibitor and 5-HT1A receptor partial agonist profile, so it has been regarded as a serotonin partial agonist-reuptake inhibitor (SPARI). We aimed to provide Vilazodone's clinical implications mainly by reviewing published clinical trials. Vilazodone has been speculated to have three potential benefits including faster onset of action, greater efficacy, and better tolerability owning to its SPARI properties. However, no studies c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 46 publications
0
20
0
1
Order By: Relevance
“…It is suggested that the dose be slowly titrated from 1 mg twice daily, by doubling the dosage daily to avoid orthostatic hypotension [42,43]. Iloperidone demonstrates high binding affinity for D 2 and D 3 receptors, α1-adrenergic receptors, and 5-HT 2 A [42]; however, receptor affinity for D 2 and 5-HT 2 A, is low compared with other antipsychotics such as lurasidone and asenapine [44]. Iloperidone demonstrates moderate affinity for α2 receptors, and therefore may have greater risk of orthostatic hypotension [45,46].…”
Section: Iloperidonementioning
confidence: 99%
See 2 more Smart Citations
“…It is suggested that the dose be slowly titrated from 1 mg twice daily, by doubling the dosage daily to avoid orthostatic hypotension [42,43]. Iloperidone demonstrates high binding affinity for D 2 and D 3 receptors, α1-adrenergic receptors, and 5-HT 2 A [42]; however, receptor affinity for D 2 and 5-HT 2 A, is low compared with other antipsychotics such as lurasidone and asenapine [44]. Iloperidone demonstrates moderate affinity for α2 receptors, and therefore may have greater risk of orthostatic hypotension [45,46].…”
Section: Iloperidonementioning
confidence: 99%
“…Iloperidone demonstrates moderate affinity for α2 receptors, and therefore may have greater risk of orthostatic hypotension [45,46]. It also shows mild antagonism on 5-HT 1A receptors [44]. Finally, it exhibits minimal affinity for H1 receptors, thus theoretically offering limited sedation and weight gain [46].…”
Section: Iloperidonementioning
confidence: 99%
See 1 more Smart Citation
“…Клинические данные, полученные на взрослых пациентах, свидетельствуют о том, что лечение депрессий комбинацией ингибитора обратного захвата серотонина (5-HT) флуоксетина и агонистов серотонинергических рецепторов типа 1А (5-HT1A-рецептор) имеет более высокий терапевтический эффект по сравнению с эффектом одного флуоксетина [13]. Действительно, флуоксетин не у каждого пациента, страдающего депрессией, вызывает улучшение состояния, более того, флуоксетин в период беременности нарушает нормальное развитие плода.…”
Section: вст уплениеunclassified
“…This can lead to increased side effects but more often to the effectiveness of a drug in a different aspect of the same disease or in more than one disease, expanding its clinical utility [Morphy and Rankovic, 2008;Wong et al, 2010]. Some others drugs were specifically, and not serendipitously, synthesized with the purpose to contemporarily bind different proteins and provide an improvement of the effectiveness (i.e., agomelatine, vilazodone) [Dawson and Watson, 2009;Guardiola-Lemaitre et al, 2014;Wang et al, 2016]. Table 1 shows some examples of drugs with their main and secondary mechanisms of action and some examples of drugs designed to contemporarily bind two different receptors involved in the same disease.…”
Section: Multitarget Drug Approach In Antipsychotic Drug Discoverymentioning
confidence: 99%